Additional de novo missense genetic variants in NALCN associated with CLIFAHDD syndrome. Issue 6 (30th January 2017) - Vivero, M.; Cho, M.T.; Begtrup, A.; Wentzensen, I.M.; Walsh, L.; Payne, K.; Zarate, Y.A.; Bosanko, K.; Schaefer, G.B.; DeBrosse, S.; Pollack, L.; Mason, K.; et al.
Abstract :